TINJAUAN YURIDIS TERHADAP PENANAMAN MODAL ASING YANG DILAKUKAN DENGAN MENGGUNAKAN METODE PEMEGANG SAHAM NOMINEE SEBAGAI PEMENUHAN SYARAT PENANAMAN MODAL ASING DIBIDANG USAHA YANG TERBUKA BERSYARAT - Daniel Daniel; Ariawan Ariawan (Jurnal Hukum Adigama, 2021)
The nominee agreement is an agreement that was born based on article 1319 of the Civil Code as this provision states that there are two types of agreements, namely: named agreements and unnamed agreements wherein this anonymous agreement is still recognized as long as it respects the provisions in force in the law. Civil law,as stipulated in the 1320 Civil Code, and recognized under Article 1338 of the Civil Code as an agreement that binds the parties so that the parties are obliged to heed this agreement in good faith. Investments carried out using the nominee method are not expressly and clearly prohibited because there are two recognized types of ownership, namely: Legal Owner or legal owner and beneficial owner as a settlor or arguably as Principal investor where the capital invested in a company comes from the settlor. as beneficiary owner. legally the name of the nominee is recorded in the articles of association of a company as the real owner before the law while the principal investor is the controller of the nominee. So it is difficult to deny that this method is one way for principal investors to circumvent the provisions and restrictions given by the government for them to control a certain number of shares. So that in its existence this type of agreement still exists and is still developing in the legal ecosystem in Indonesia.